Ultrasound-Guided Centrally Inserted Central Catheter (CICC) Placement in Newborns: A Safe Clinical Training Program in a Neonatal Intensive Care Unit - Tommaso Zini; Lucia Corso; Cinzia Mazzi; Cecilia Baraldi; Elisa Nieddu; Laura Rinaldi; Francesca Miselli; Luca Bedetti; Eugenio Spaggiari; Katia Rossi; Alberto Berardi; Licia Lugli; et al. (MDPI AG, 2024)
Background: Centrally inserted central catheters (CICCs) are increasingly used in neonatal care. CICCs have garnered attention and adoption owing to their advantageous features. Therefore, achieving clinical competence in ultrasound-guided CICC insertion in term and preterm infants is of paramount importance for neonatologists. A safe clinical training program should include theoretical teaching and clinical practice, simulation and supervised CICC insertions. Methods: We planned a training program for neonatologists for ultrasound-guided CICCs placement at our level III neonatal intensive care unit (NICU) in Modena, Italy. In this single-centre prospective observational study, we present the preliminary results of a 12-month training period. Two paediatric anaesthesiologists participated as trainers, and a multidisciplinary team was established for continuing education, consisting of neonatologists, nurses, and anaesthesiologists. We detail the features of our training program and present the modalities of CICC placement in newborns. Results: The success rate of procedures was 100%. In 80.5% of cases, the insertion was obtained at the first ultrasound-guided venipuncture. No procedure-related complications occurred in neonates (median gestational age 36 weeks, IQR 26-40; median birth weight 1200 g, IQR 622-2930). Three of the six neonatologists (50%) who participated in the clinical training program have achieved good clinical competence. One of them has acquired the necessary skills to in turn supervise other colleagues. Conclusions: Our ongoing clinical training program was safe and effective. Conducting the program within the NICU contributes to the implementation of medical and nursing skills of the entire staff.